The Meaning of Rationalization: An Analysis of the Literature - Brady, Robert A. (Quarterly Journal of Economics, 1932)
Journal Article The Meaning of Rationalization: An Analysis of the Literature Get access Robert A. Brady Robert A. Brady University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 3, May 1932, Pages 526–540, https://doi.org/10.2307/1883398 Published: 01 May 1932